New species of Pseudocercospora associated with leaf spot in forest flora of India and Nepal - and KAMAL, H.S.G. RAO, ARCHANA SINGH (Indian Phytopathology, 2002)
P. ailanthigena on Ailanthus excelsa, P. brideligena on Bridelia stipularis and P. rauwolfiae-serpentinae on Rauvolfia serpentina are described and compared with allied species. P. brideligena was collected from Nepal and P. ailanthigena and P. rauwolfiae-serpentinae were collected from the forest flora of North-Eastern Uttar Pradesh in India.